The mechanisms of resistance to second- and third-generation ALK inhibitors and strategies to overcome such resistance. Issue 9 (2nd September 2021) - Haratake, Naoki; Toyokawa, Gouji; Seto, Takashi; Tagawa, Tetsuzo; Okamoto, Tasuro; Yamazaki, Koji; Takeo, Sadanori; Mori, Masaki
ABSTRACT: Introduction: Anaplastic lymphoma kinase (ALK) inhibitors are widely known to contribute to the long-term survival of ALK -rearranged non-small cell lung cancer (NSCLC) patients. Based on clinical trial data, treatment with second- or third-generation ALK inhibitors can be initiated after crizotinib therapy without analyzing resistance mechanisms, and some randomized trials have recently shown the superiority of second- or third-generation ALK inhibitors over crizotinib as the initial treatment; however, the optimal treatment for patients who relapse while on second- or third-generation ALK inhibitors is not well-defined. Areas covered: This review provides an overview of the mechanisms of resistance to second- or third-generation ALK inhibitors that have been identified in both clinical and pre-clinical settings, and introduces strategies for overcoming resistance and discusses ongoing clinical trials. Expert opinion: The comprehensive elucidation of both ALK -dependent and ALK -independent resistance mechanisms is necessary to improve the prognosis of patients with ALK -rearranged NSCLC. Liquid biopsy to clarify these mechanisms of resistance might play an important role in the near future.